Crime as an assemblage - Crockett Thomas, Phil (Journal of Theoretical and Philosophical Criminology, 2020)
This article seeks to make an original contribution to criminology and the sociology of crime and punishment by elaborating the ‘assemblage’, a concept which originates in the collaborative poststructuralist philosophy of Gilles Deleuze and Félix Guattari and discussing its ontological implications for researching crime. I will first introduce the concept and its application. I then discuss the relationship between the assemblage and Michel Foucault’s concept of the dispositif. I demonstrate how the assemblage could be used to analyse crime events and discuss questions of change and scale within the assemblage. I conclude by outlining some implications for how adopting this concept would change the way we practice and research crime and punishment.